The Shallot Growth and Yield from True Shallot Seed using Biochar, Compost, and Organic Pesticide in Wanasari, Brebes Regency - Triyani Dewi; Edhi Martono; Eko Hanudin (JURNAL PANGAN, 2023)
The practice of environmentally friendly shallot cultivation is nowadays widely applied by farmers, beside reducing environmental contamination and producing agricultural products that are safe for consumption, it can also increase shallot production. This study aimed to determine the effect of biochar, compost, and organic pesticides on the growth and yield of shallot, and the activity of microorganisms in the soil. The study was conducted in Klampok Village, Wanasari, Brebes Regency from January to July 2020 using a complete randomized block design with nine treatments which were a combination of biochar, compost, organic pesticides, recommended dose of pesticides, and farmers’ dose of pesticides. The shallot seed used was the Bima Brebes variety. Soil characteristics, compost nutrient contents, plant growth, shallot yield, and total soil bacteria population were measured. The study showed that the yield of shallot was 16.7 tons/ha obtained from adding compost and recommended doses of pesticides. The treatment of biochar, compost, and organic pesticides, although it has not been able to increase the growth and yield of shallot, it can be applied for shallot cultivation as it can increase the total bacterial population of soil, reduce the use of chemical pesticides, reduce production input costs, and environmentally friendly.